Colorimetric oxygen indicator films based on β‐cyclodextrin grafted chitosan/montmorillonite with redox system for intelligent food packaging - Thanatcha Jarupatnadech; Jongjit Chalitangkoon; Pathavuth Monvisade (Packaging Technology and Science, 2022)
Oxygen is an important factor in food deterioration; thus, packaging, with an in‐built oxygen indicator, has been widely developed. Here, a safer, natural product‐based, colorimetric oxygen indicator film based on β‐cyclodextrin grafted chitosan/montmorillonite with methylene blue/glucose system was fabricated. Methylene blue in the activated films was reduced to leuco‐form (colourless) by glucose and reverted to blue with oxygen exposure. Glucose, as well as the reducing agent for methylene blue, crosslinked the chitosan. In addition, the grafting of β‐cyclodextrin onto chitosan and the addition of montmorillonite as well as humidity led to the faster colour changes of the films. The colour recovery of films could delay by covering them with a poly(ethylene terephthalate) (PET) film. The activated films showed good storage stability at low temperature which is suitable for the package of refrigerated food products. The films had the potential to be used as natural‐based colorimetric oxygen indicators for food packaging.
Keywords: Analytical Chemistry and Sensors; Conducting polymers and applications; Nanocomposite Films for Food Packaging